Influencer, Price Discount, and Product Quality: Their Impact on Impulse Buying Behavior of Millennial and Gen Z Consumers - Pratono, Febrina Kinanti; Prabandari, Sri Palupi (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
This research aims to determine the influence of Influencers, Price Discounts, and Product Quality on Impulse Buying among Generation Millennial and Generation Z TikTok Shop consumers in Malang City. The influence intended in this research is the influence that occurs either directly or indirectly between the independent variable and the dependent variable. This type of research is explanatory research using a quantitative approach. The sampling technique used was non-probability sampling with a purposive method for 150 respondents who came from the generation millennial and generation Z TikTok Shop consumer population in Malang City and had made transactions at least twice or more. The data analysis used was IBM SPSS 26.0. The results of this research explain that influencers can make a positive contribution to encouraging an increase in impulse buying, price discount is able to make a positive contribution to increasing impulse buying, and product quality builds a positive relationship contribution to increasing impulse buying.